2022
DOI: 10.3389/fvets.2022.801800
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Mechanism of Resistance of Tulathromycin Against Mycoplasma hyopneumoniae in a PK/PD Model and the Fitness Costs of 23S rRNA Mutants

Abstract: Macrolides are widely used in diseases caused by Mycoplasma spp. The new semi-synthetic macrolide antibiotic tulathromycin is currently in wide use for the treatment of respiratory diseases of livestock. The objective of this study was to evaluate the antibacterial effect of tulathromycin against Mycoplasma hyopneumoniae using an in vitro pharmacokinetic/pharmacodynamic (PK/PD) model to reveal mechanisms of antibiotic resistance and to evaluate the fitness of drug-resistant strains. In this study, high perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The high resistance to fosfomycin suggests that the dose of the drug needs to be strictly controlled clinically. 32 Recent studies on vancomycin in the treatment of enterococcal infection revealed that parameters such as AUC/MIC and valley concentration can guide the concentration control of vancomycin, thereby improving treatment results and reducing side effects such as nephrotoxicity. 71 , 72 This suggests that we need to conduct in-depth studies of relevant PK/PD models to identify drug-related therapies and resistance targets to optimize the clinical choice of individualized doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high resistance to fosfomycin suggests that the dose of the drug needs to be strictly controlled clinically. 32 Recent studies on vancomycin in the treatment of enterococcal infection revealed that parameters such as AUC/MIC and valley concentration can guide the concentration control of vancomycin, thereby improving treatment results and reducing side effects such as nephrotoxicity. 71 , 72 This suggests that we need to conduct in-depth studies of relevant PK/PD models to identify drug-related therapies and resistance targets to optimize the clinical choice of individualized doses.…”
Section: Discussionmentioning
confidence: 99%
“…Where RF is the number of resistant bacteria at the end of culture, RI is the number of resistant bacteria before culture, SF is the number of susceptible bacteria at the end of culture, and SI is the number of susceptible bacteria before culture. W < 1 indicates that the competitive fitness of S is better than that of R, W = 1 indicates that the competitive fitness of S and R is similar, and W > 1 indicates that the competitive fitness of R is better than that of S. 32 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous reports ( 21 23 ), an in vitro model compatible with M. gallisepticum growth and amphenmulin pharmacokinetics was developed ( 24 ). It comprised a reservoir chamber containing fresh, drug-free medium; a reaction chamber with a three-necked flask where amphenmulin interacts with M. gallisepticum , containing 300 mL of medium in the outer chamber (external compartment, EC) and 10 mL of M. gallisepticum culture (10 7 CFU/mL) in a semipermeable membrane chamber (internal compartment, IC); and a waste chamber collecting effluent, which were connected via tubing and controlled by a peristaltic pump ( Fig.…”
Section: Methodsmentioning
confidence: 99%